Testimonios of Antiracist School Social Workers: Advancing Professional Equity and Updating the School Social Work Model. - Sosa, Leticia Villarreal; McCoy, Christy; Thompson, Laurel E; Ochocki, Stephanie (Children & Schools, 2025)
During a modern era of rising white nationalism and racial reckoning, the opportunity to reimagine the national model for school social work practice was explored in partnership with practitioners, scholars, researchers, and leaders of the profession. It sparked a parallel process of engagement that required the critical analysis of the systemic and structural racism impacting not only our educational communities, but also the historical influences shaping the school social work profession. Like the many antiracist efforts that have come before, the revision process was impacted by a pervasive culture of white supremacy, yet what emerged was an equity-centered model to guide the school social work profession into the future. The present article explores the collective experience, inclusive of reflective self-examination of lived experiences and guided by professional values and ethical responsibilities, which resulted in a practice model that seeks to transform inequities that prevent students and schools from achieving their optimal well-being. With its emphasis uplifting diversity, equity, inclusion, justice, and belonging, the National School Social Work Practice Model 2.0 centers the students and communities we seek to serve and propels the profession toward partnership in creating a liberatory future for all.